Unpacking Fair Trade bananas and coffee: private financial investment and the state in Costa Rica. Issue 7 (3rd October 2021) - Zaglul Ruiz, Layla; Luetchford, Peter
ABSTRACT: Entanglements between the state and agricultural production played a central role in determining the implementation of Fair Trade in the coffee and banana industries in Costa Rica. This paper contrasts a national imaginary of smallholder coffee production with a banana enclave dominated by US corporations. While the former complements Fair Trade practices, the latter precludes its entry into the sector except under exceptional circumstances. However, in neither case are structural inequalities eliminated; they are rather reproduced. The article shows that divergent historical circumstances frame how these industries operate and thereby directly impact Fair Trade as a private sector development initiative.